Neural Subtype Specification from Embryonic Stem Cells - Zhang, Su‐Chun (Brain Pathol, 2006)
One of the keys to using embryonic stem cells (ESCs) in brain research and potential application in neurological diseases is directed differentiation of neuronal and glial subtypes. This may be achieved by application of developmental principles in guiding cell lineage specification from naïve stem cells. Establishment of defined ESC differentiation models that recapitulate in vivo development, especially from human ESCs, will most likely provide a dynamic tool for dissecting molecular mechanisms underlying early embryonic development that is otherwise not readily obtainable. This is also a rational and realistic way of producing enriched populations of functional neurons and glia for pathological analyses as well as possible therapeutic applications.